Етичний аспект криминально - процесуальних відносин слідчого з суб'єктами кримінального процесу. - Гуртієва, Л.М.; Гуртиева, Л.М.; Gurtieva, L. (My University, 2012)
The article is devoted ethical problems of investigator’s criminal-procedural relations with subjects of criminal procedural. A particular attention is paid to the problems of prevention, elimination of the conﬂ ict situation, resolving of the criminal-procedural conﬂ ict by investigator. Proposals for improvement of acting criminal-procedural legislation and practice of its implementation are presented.
Гуртієва Л.М.Етичний аспект криминально - процесуальних відносин слідчого з суб'єктами кримінального процесу. / Л.М. Гуртіева //Актуальні проблеми політики : зб. наук. пр. / гол. ред. С. В. Ківалов ; відп. за вип. Л. І. Кормич. – Одеса : Національний університет "Одеська юридична академія" : Південноукраїнський центр гендерних проблем,2012.–Вип.44.C. 342 - 351.
Keywords: Кримінально - процесуальні відносини; Кримінальний процес; Суб'экти кримінального прцеса; Етичні проблеми слідчого з суб'єктами кримінального процесу; Этические проблемы следователя с субъектами уголовного процесса; Субъекты уголовного процесса; Уголовный процесс; Уголовно - процессуальные отношения; Criminal - procedural relations; criminal process; Subjects of the criminal process; Ethical problems investigator with the subjects of criminal proceedings